The effect of self-care education on the control of diabetes complications, medications and HbA1C in adolescents with type 1 diabetes - Mahdieh Azizi; Narges Arsalani; Farahnaz Mohammadi Shahboulaghi; Samaneh Hosseinzadeh; Asadollah Rajab (Tehran University of Medical Sciences, 2017)
Background & Aim: Diabetes is a chronic disease that needs lifelong special self-care behaviors. Adolescents with type 1 diabetes need self-care education for the control of diabetes and the prevention of its complications. Therefore, this study aimed to determine the impact of self-care education on the control of diabetes complications, medications and HbA1C in adolescents with type 1 diabetes. Methods & Materials: This study is a non-randomized clinical trial (IRCT2015051322258N1) carried out on seventy four adolescents aged 12-18 years old with type 1 diabetes referred to the Iran diabetes association. They were selected using convenience sampling method and allocated into two groups (intervention: 34 people, control: 40 people). An educational intervention was performed in five sessions for the intervention group. After education, the patients were trained and followed up using mobile services for three months. The instruments consisted of a demographic characteristics form and a section of the self-care behaviors scale evaluating medications and the control of complications. Data were analyzed by the SPSS software v.18. Results: Before the education, no significant difference was observed in the mean scores of medications and control of complications and level of HbA1C between the two groups of intervention and control (P>0.05). After the education, there was a significant difference between two groups in the mean scores of medications and control of complications and level of HbA1C (P<0.05). Conclusion: Self-care education and the follow up after educational sessions can lead to the reduction in diabetes complications and HbA1C level among adolescents with type 1 diabetes. Background & Aim: Diabetes is a chronic disease that needs lifelong special self-care behaviors. Adolescents with type 1 diabetes need self-care education for the control of diabetes and the prevention of its complications. Therefore, this study aimed to determine the impact of self-care education on the control of diabetes complications, medications and HbA1C in adolescents with type 1 diabetes. Methods & Materials: This study is a non-randomized clinical trial (IRCT2015051322258N1) carried out on seventy four adolescents aged 12-18 years old with type 1 diabetes referred to the Iran diabetes association. They were selected using convenience sampling method and allocated into two groups (intervention: 34 people, control: 40 people). An educational intervention was performed in five sessions for the intervention group. After education, the patients were trained and followed up using mobile services for three months. The instruments consisted of a demographic characteristics form and a section of the self-care behaviors scale evaluating medications and the control of complications. Data were analyzed by the SPSS software v.18. Results: Before the education, no significant difference was observed in the mean scores of medications and control of complications and level of HbA1C between the two groups of intervention and control (P>0.05). After the education, there was a significant difference between two groups in the mean scores of medications and control of complications and level of HbA1C (P<0.05). Conclusion: Self-care education and the follow up after educational sessions can lead to the reduction in diabetes complications and HbA1C level among adolescents with type 1 diabetes.